The future of the dollar as an international currency - Aliber, Robert Z. (New York : F.A. Praeger, 1966)
This book, written from the United States point of view reviews the historical development of the dollar as an international currency, and concludes from an assessment of the costs and benefits to the United States of the reserve-currency status of the dollar that, up to now at least, the benefits have outweighed the costs. The book further discusses three aspects of the international financial problem: the process of balance-of-payments adjustment, the adequacy of reserves, and the stability of an international monetary system characterized by a multiplicity of reserve assets.
Includes bibliographical footnotes.
usc 20/08/18
Loans
Keywords: International finance; Balance of payments; Currency question; United States